Role of Mothers’ Expressed Emotions in Psychopathology and Social-Emotional Competence in Adolescents - Akhtar, Shammem; Zaqia Bano (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the role of mothers’ expressed emotions in psychopathology and social-emotional competence in adolescents.Study Design: Cross sectional study.Place and Duration of Study: Department of Psychology, University of Gujrat, Gujrat Pakistan, from Jul 2020 to Aug 2021Methodology: Five hundred mothers and their five hundred adolescents were approached to measure the role of mothers’expressed emotions in psychopathology and social-emotional competence in adolescents. For this purpose, parental Expressed Emotions Scale-1 was used, and to assess the psychopathology and social-emotional competence in adolescents, Social Anxiety Scale-2 and Social-Emotional Competence Scale-3 were used.Results: Artificial neural network (ANN) analysis was used to identify the mothers' expressed emotions as predictors of social anxiety and social-emotional competence in adolescents. Results showed incorrect predictions was for training data (60%) and for testing data (28%), which signify the current results that around 72% of right decision about mothers’ expressed emotions as a predictor of social anxiety and social-emotional competence in adolescents.Conclusion: In the teenage period, youth face an increasing number of psychological, social, and developmental challenges. Mothers are the first teachers of their children. When they fail to support them and display ways of negatively expressing emotions, it leads to overall mental health issues, in which social anxiety is the most common challenge.